2020
DOI: 10.1074/jbc.ra119.012144
|View full text |Cite
|
Sign up to set email alerts
|

Structure-function relationships of the soluble form of the antiaging protein Klotho have therapeutic implications for managing kidney disease

Abstract: The fortuitously discovered antiaging membrane protein αKlotho (Klotho) is highly expressed in the kidney, and deletion of the Klotho gene in mice causes a phenotype strikingly similar to that of chronic kidney disease (CKD). Klotho functions as a co-receptor for fibroblast growth factor 23 (FGF23) signaling, whereas its shed extracellular domain, soluble Klotho (sKlotho), carrying glycosidase activity, is a humoral factor that regulates renal health. Low sKlotho in CKD is associated with disease progression, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 67 publications
0
22
0
1
Order By: Relevance
“…CKD is characterized by persistent ER stress that yields increased accumulation of misfolded or unassembled proteins (including Klotho) in the ER. Because Klotho contains eight putative N-linked glycosylation sites, it is presumably subjected to post-translational modifications before maturation [5]. As an important compensatory mechanism, ERAD is activated to alleviate protein overload and maintain normal cell function in the context of persistent ER stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CKD is characterized by persistent ER stress that yields increased accumulation of misfolded or unassembled proteins (including Klotho) in the ER. Because Klotho contains eight putative N-linked glycosylation sites, it is presumably subjected to post-translational modifications before maturation [5]. As an important compensatory mechanism, ERAD is activated to alleviate protein overload and maintain normal cell function in the context of persistent ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…mKlotho is a type 1 transmembrane glycoprotein with a short intracellular domain, membrane spanning domain, and large extracellular domain. sKlotho is produced by ectodomain shed of mKlotho or alternative Klotho mRNA splicing [5]. Because Klotho is mainly generated by the kidney, it is easily understood that Klotho expression is influenced by the state of kidney function [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…β1,4GalNAcT3 [ 51 ] and β1,4GalNAcT4 [ 52 ] account for GalNAc transfer and have a broad tissue expression coverage including fetal kidney and brain. It has been reported that adding a carboxyl-terminal 19-amino-acid α-helix stretch with several basic amino acids is sufficient to mediate GalNAc transfer to N-linked oligosaccharides [ 47 , 53 , 54 ]. Other GalNAc motifs involve three structural loops with aromatic side chains [ 50 ], as well as additional unidentified motifs [ 54 ].…”
Section: Galnac Binder—a New Application Based On Previous Findingsmentioning
confidence: 99%
“…Each domain had weak homology to the family 1 glycosidases. It is still controversial whether Klotho protein has enzymatic activity as a glycosidase [42][43][44][45][46], because two conserved catalytic glutamate residues essential for the glycosidase activity and thus conserved in all the family 1 glycosidases are replaced with other amino acids in Klotho protein.…”
Section: Phosphate and Ageingmentioning
confidence: 99%